Implementasi Nilai Syariah Pada Aktivitas Corporate Social Responsibility PT. BNI Syariah Jakarta - Beta Raditya Aulia; Irham Zaki (Universitas Airlangga, 2015)
Implementation of Corporate Social Responsibility in Islamic banking refers to a business that has a social responsibility in Islamic. Islamic values contained in CSR activity that is the values of justice, Rohmatan lil'alamin value, and the value maslahah. That understanding will have implications for the implementation of syariah in the CSR value BNI Syariah Jakarta. The research method which is used for this case is qualitative descriptive approach. This Research is using semi-structured interviews and documentation. This Research was concern on the syariah value of CSR activities BNI Syariah Jakarta and find out for the solutiaon on how the implementation of sharia value on CSR activities BNI Syariah Jakarta. The results of this research was indicated that the PT. BNI Syariah Jakarta has implemented three grades sharia Islamic banking in performing activities of corporate social responsibility, which has implemented sharia values of justice, Rohmatan li'alamin value, and the value maslahah with full responsibility and in accordance to sharia compliance or regulations.